Synthesis of Organo-Quartz from Lumajang Sea Sand Using Sodium Dodecyl Benzene Sulfonate (SDBS) Modificator for Adsorption of Fe3+ - Dhimas Yudistira; Danar Purwonugroho; Tutik Setianingsih (The Journal of Pure and Applied Chemistry Research, 2021)
This study aims to determine the effect of sea sand modification with SDBS for adsorption of Fe3+. Sea sand was treated with 0.1 M HCl solution at 25oC. Organo-quartz was prepared at SDBS concentration of below, equal, and above the CMC value by shaking the mixture for 4 hours at 100 rpm. Characterization by FTIR spectrophotometry showed a change in the spectra pattern. The activation caused increasing of -OH silanol while modifications make them decrease. Characterization with SEM showed that the morphology of the sea sand was not uniform with irregular white chunks. The EDX results showed that the dominant elements were C (13.89% ± 10.86), O (40.48% ± 6.58), Si (16.51% ± 8.13), and Fe (11.68% ± 14.38). Adsorption was carried out using Fe3+ at 50 ppm. The Fe3+ analysis was conducted by AAS. The adsorption value by activated sea sand was 58.22% ± 7.23% whereas without treatment sea sand was 70.46% ± 5.54, and the modified sea sand was 53.24% ± 4.86. The lower adsorption is probably caused by the dissolved iron oxides in sea sand during activation.